Stress to your advantage - WGBH (Television station : Boston, Mass.) (Northbrook, Illinois Coronet MTI Film & Video, 1986)
What is the secret to stress-resistant "hardiness?" Viewers can assess their ability to deal with stress and learn to recognize and control the aggravations that wear them down.
Distributed by International Book Center.
With 1 converted disc.
James "Red" Duke Jr., co-hosted by Judith Rodin and T. George Harris.
Keywords: Stress (Psychology); Stress, Psychological